2017
DOI: 10.1159/000458705
|View full text |Cite
|
Sign up to set email alerts
|

Paramedian Thalamic Ischemic Infarction: A Retrospective Clinical Observation

Abstract: Background: The study aimed to evaluate the clinical features in patients with bilateral and unilateral paramedian thalamic infarcts. Methods: Twenty-one patients with paramedian thalamic infarcts were included, and their case records were reviewed. We focused on the patients' neuroimaging and neurological symptoms including the duration of coma, vertical gaze palsy, and memory impairment. The causes of bilateral and unilateral paramedian thalamic infarcts were also investigated. Result: Nine patients had bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Damage to the intralaminar thalamic nuclei, which receive a dense NA innervation ( Figs 3 – 6 , Table 3 ), is reckoned as one of the causes for the pathological loss of consciousness ( Castaigne et al . 1981 ; Lin et al . 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the intralaminar thalamic nuclei, which receive a dense NA innervation ( Figs 3 – 6 , Table 3 ), is reckoned as one of the causes for the pathological loss of consciousness ( Castaigne et al . 1981 ; Lin et al . 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and fundamental investigations on the implication of thalamic lesions on regards to arousal, led to contrasting results with either loss (3,4,55) or no changes in arousability (56,57). Here, we took advantage of the optical fibre technology for better temporal and spatial infarct resolution to investigate the functional consequences of IL Opto-STROKE.…”
Section: Histological Characterization Of Optical Mini-stroke (Opto-stroke) In Thalamic Regionsmentioning
confidence: 99%
“…In 5 patients with bilateral paramedian infarction and 4 patients with unilateral paramedian infarction, coma, vertical eye movement impairment and memory impairment were detected. As a result, they reported that paramedian infarctions leads to coma, vertical eye movement impairment and memory impairment in both unilateral and bilateral groups [22]. In another study, it was reported that patients with paramedian infarction had hypersomnia, lack of daytime wakefulness and impaired night sleep stages [23].…”
Section: Discussionmentioning
confidence: 99%